Physical functionalization of multi-walled carbon nanotubes for enhanced dispersibility in aqueous medium - Mohamed Youssry (14158971) (2020)
Noncovalent functionalization of multi-walled carbon nanotubes (MWCNTs) by anionic surfactants (sodium dodecylbenzene sulfonate; SDBS and sodium cholate; SC) results in stable aqueous dispersions. SDBS showed better dispersing efficiency at lower concentration than that of SC due to the stabilizing π-π stacking induced by the presence of benzene ring in the tail of SBDS. The hemimicelle formation on the surface of nanotubes is likely to be the dominant dispersion mechanism that imparts higher colloidal stability for the MWCNTs in aqueous medium. Other Information Published in: Emergent Materials License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s42247-020-00076-3